AVAILABILITY AND UTILIZATION OF AGRICULTURAL FOOD AS A SOURCE OF BALI BEEF IN MOWEWE SUB-DISTRICT, EAST KOLAKA - Asya, Nur; Nafiu, La Ode; Hafid, Harapin (Pascasarjana Universitas Sulawesi Tenggara, 2021)
This study aims to analyze the availability and utilization of agricultural by-products as a source of feed for Balinese cattle in Mowewe District, East Kolaka Regency. The research was conducted in March-May 2020. The research respondents involved 83 cow breeders. The data analysis used is descriptive analysis. The availability of agricultural food waste feed is calculated based on the formula Muller et al. (1974). The variables observed were the type of feed from agricultural byproducts and the potential availability of agricultural by-products as feed for Bali cows in Mowewe Sub-district, East Kolaka Regency. The results showed thatwith the production of forage BK/Ha 167602.80 tons/year. The availability and use of agricultural by-products as a source of feed for Bali cattle include:Type of feed from agricultural by-products, namely rice straw, sweet potato, maize and peanuts. Potential availability of agricultural by-products as feed, namely, agricultural by-products in the research location for producing rice straw.2073.75 tons/year, 6000 tons/year of sweet potato waste, 54000 tons of corn waste/year and 6000 tons of peanut waste/year.